Homer takes the Streetcar – The Modernist Appropriation of the Epic and Alfred Döblin's Berlin Alexanderplatz - Christian Sieg (Forum, 2006)
In this article, I will show how Alfred Döblin is, on the one hand, captivated by the extensiveness of the traditional epic - a quality which Hegel in his Lectures on Fine Arts highlights and which is often terminologically expressed as 'epic breadth' - whilst on the other hand, Döblin is fascinated by the oral character of the antique genre. I will also explore how both these qualities are fundamentally altered in Döblin's modernist appropriation of the epic. Since the heroic deeds, which the antique epic extensively addresses, are at odds with modern sensibilities, Döblin transforms the epic into a modernist encyclopaedia of ordinary practices.